2002
DOI: 10.1063/1.1483848
|View full text |Cite
|
Sign up to set email alerts
|

Excited-state dynamics of alizarin-sensitized TiO2 nanoparticles from resonance Raman spectroscopy

Abstract: Resonance Raman spectra of alizarin-sensitized TiO2 nanoparticles have been obtained at excitation wavelengths throughout the 488-nm charge transfer absorption band. The resonance Raman spectrum of the alizarin-sensitized TiO2 nanoparticle is significantly different from the spectrum of free alizarin, consistent with a chemisorption-type interaction. This interaction is probably chelation of surface titanium ions by the hydroxy groups of alizarin, supported by the observed enhancement of bridging C–O modes at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
105
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(122 citation statements)
references
References 57 publications
16
105
1
Order By: Relevance
“…6, 11 Similarly, a strong feature at 1331 cm −1 , attributed to a C-O stretching mode, indicates the vital role of the catecholate functionality in providing bridging adsorption. 18 …”
Section: Resultsmentioning
confidence: 99%
“…6, 11 Similarly, a strong feature at 1331 cm −1 , attributed to a C-O stretching mode, indicates the vital role of the catecholate functionality in providing bridging adsorption. 18 …”
Section: Resultsmentioning
confidence: 99%
“…However, it is not altogether straightforward to determine if such complexes exist and if their excitations (as opposed to excitation of an inherent local transition in the dye) contribute to electron injection. Taking the alizarin-TiO 2 system as an example, both Ramakrishna et al [675], and Shoute and Loppnow [657] proposed that a charge transfer complex between alizarin and the TiO 2 surface formed on adsorption and excitation of this complex led to the observed electron injection. The latter authors estimated that the TiO 2 nanoparticle surface used in their studies experienced the majority of the observed reorganization energy (∼0.32 eV total) that resulted from this process based on a fluorescence Stokes shift seen after excitation.…”
Section: Excited Electron Donor To Tio 2 Conduction Bandmentioning
confidence: 97%
“…46 The general implementation of these equations for absorption and resonance Raman spectroscopy has been described in detail previously. 47,48 We have used the strongly overdamped and high temperature (pΛ , kT) limits in our analysis. The Journal of Physical Chemistry B ARTICLE We used initial guesses for the displacements along each normal coordinate (Δ) that were based on the assumption that the average relative resonance Raman intensities are proportional to Δ 2 , with the intensity of the 1343 cm À1 mode set arbitrarily to 1.…”
Section: ' Theorymentioning
confidence: 99%